2015
DOI: 10.1159/000380751
|View full text |Cite
|
Sign up to set email alerts
|

Binaural Auditory Outcomes in Patients with Postlingual Profound Unilateral Hearing Loss: 3 Years after Cochlear Implantation

Abstract: The value of cochlear implants (CI) in patients with profound unilateral hearing loss (UHL) and tinnitus has recently been investigated. The authors previously demonstrated the feasibility of CI in a 12- month outcome study in a prospective UHL cohort. The aim of this study was to investigate the binaural auditory outcomes in this cohort 36 months after CI surgery. The 36-month outcome was evaluated in 22 CI users with postlingual UHL and severe tinnitus. Twelve subjects had contralateral normal hearing (singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 26 publications
4
62
0
4
Order By: Relevance
“…The SSQ is a standardized, hearing disease-specific questionnaire in which the responder is asked to assess their hearing ability with reference to a variety of realistic, real-world listening situations . The SSQ was chosen as it has been reported to be sensitive to changes in hearing function following treatment with a variety of hearing therapies, implantable and nonimplantable hearing devices, and stimulation configurations [Noble and Gatehouse, 2006;Noble et al, 2008;Laske et al, 2009;House et al, 2010;Noble, 2010;Pai et al, 2012;Mertens et al, 2015]. While many versions of the SSQ exist, the English version 5.6 with 49 questions, available online from the British Medical Research Council, was used as a master version for subsequent validated translations to German, Spanish, Polish, and Afrikaans.…”
Section: Main Outcome Measures Health Utilities Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSQ is a standardized, hearing disease-specific questionnaire in which the responder is asked to assess their hearing ability with reference to a variety of realistic, real-world listening situations . The SSQ was chosen as it has been reported to be sensitive to changes in hearing function following treatment with a variety of hearing therapies, implantable and nonimplantable hearing devices, and stimulation configurations [Noble and Gatehouse, 2006;Noble et al, 2008;Laske et al, 2009;House et al, 2010;Noble, 2010;Pai et al, 2012;Mertens et al, 2015]. While many versions of the SSQ exist, the English version 5.6 with 49 questions, available online from the British Medical Research Council, was used as a master version for subsequent validated translations to German, Spanish, Polish, and Afrikaans.…”
Section: Main Outcome Measures Health Utilities Indexmentioning
confidence: 99%
“…As pointed out by researchers such as Mertens et al [2015], auditory disability cannot be measured or reliably predicted based on laboratory testing of speech outcomes alone, but real-world measures such as questionnaires like the SSQ should be included to assess the preimplantation and posttreatment effects on hearing function over time.…”
Section: Longitudinal Ssq Outcomesmentioning
confidence: 99%
“…Further, the benefits derived from each device use should be comparable across device options, including the nontreatment option. Studies have been done to this end [Arndt et al, 2017;Jacob and Stelzig, 2011;Mertens et al, 2015Mertens et al, , 2016aTávora-Vieira et al, 2013a, 2015Van de Heyning et al, 2008;Vermeire and Van de Heyning, 2009], and systematic reviews of the available literature have found that a CI can provide adults with SSD or AHL with better speech perception in spatially separated noise, better sound localization, better QoL, and a decreased severity and incidence of tinnitus [Arndt et al, 2011;Tokita et al, 2014;van Zon et al, 2015;Vlastarakos et al, 2014] than a CROS-HA, BAHA, or nontreatment. This may not be surprising if one considers that the CI is the only device that reinstates the auditory input from the deaf side, hence providing the possibility to re-engage the binaural system.…”
Section: Introductionmentioning
confidence: 99%
“…Hazrati e Loizou (2012) avaliaram o efeito combinado da reverberação e ruído na inteligibilidade da fala em 11 usuários de implante coclear. Hazrati et al (2013) Mertens et al (2015) somente após 36 meses. Esses ganhos incluem a localização da fonte sonora quando expostos a ruído (Grossmann et al, 2016) e melhora da inteligibilidade mesmo na presença de ruído na orelha de audição normal (Hoth et al, 2016).…”
Section: Discussão Da Casuísticaunclassified
“…Esse dispositivo eletrônico transforma a estimulação sonora em sinais elétricos que excitam diretamente as fibras nervosas remanescentes da cóclea e que, via nervo auditivo, são conduzidos para serem decodificados pelo córtex cerebral (Buckey et al, 2001). Nos últimos anos as indicações de implante tem se ampliado e pacientes com surdez unilateral também tem sido implantados (Sampaio et al, 2011;Arndt et al, 2011;Mertens et al, 2015;Grossmann et al, 2016;Hoth et al, 2016;Sladen et al, 2017).…”
Section: Introductionunclassified